MASALAH DAN TANTANGAN PRIVATISASI PENDIDIKAN TINGGI - Nurika Khalila Daulay (JURNAL TARBIYAH, 2014)
The privatization of higher education is often understood as the commercialization of education, where higher education turned into a business area that applies economic principles "with as little capital as possible to generate maximum profit". The result is the concentration of educational institutions will be split to the thoughts and activities of "business" that will automatically change the academic shades directly or indirectly. Particularly in the context of higher education as public goods should be served not only to carry out the transfer and transmission of knowledge and expertise, but also shape the personality and character of the students and the nation